The Effect of Training and Competence on Job Satisfaction (Study on Employees at The Subdistrict Office Lengkong Bandung City) - Rosiana, Yulia; Komar Priatna, Deden; Suryaman, Suryaman (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Lengkong District Office of Bandung City as the implementing element of the Regional Government Policy in Bandung in terms of implementing services directly to the community. Optimization of job satisfaction is also related to the new Bandung City regional regulations relating to compensation or benefits for improving the performance of each employee, so that the implementation of a government performance is able to provide service to stakeholders and the community in a prime and transparent and accountable manner. But in reality there is job satisfaction for employees of the Lengkong District Office in Bandung City is still not optimal when viewed from the main tasks and functions that are the responsibility. This is evidenced by the finding of conditions regarding the implementation of training programs that are structural and functional in nature that have not been optimally implemented and competencies that are not according to their abilities. The purpose of this study is to describe training, competence, and job satisfaction and analyze the effect of training and competency on employee job satisfaction. The method used is descriptive survey method and explanatory survey. The type of investigation in this study is causality. The unit of analysis of employees of the Lengkong District Office in Bandung City with a population of 32 employees. Time horizon in this study is cross sectional and the analytical method used is frequency distribution and path analysis. Based on the results of the research and discussion, it can be found that the implementation of the training is quite in accordance with the needs of the organization. the competencies of the employees are quite appropriate. Training and competencies jointly affect employee job satisfaction, but when viewed partially, it turns out that training has a more dominant influence on employee job satisfaction than competence.